The Mask and Agamben: the Transitional Juridical Technics of Legal Relation - Connal Parsley (Law Text Culture, 2010)
Italian theorist Giorgio Agamben is well known for his complex critique of the institution and praxis of thought in the west, and in particular for taking aim at a constellation of ontologico-political structures denoted by the term ‘juridical’. Within this endeavour, Agamben provides a critique of the metaphysical subject and of the related notion of the person. Specifically, for Agamben the figure of the human is structured and produced by the dignitas: the image or mask which bridges the juridical, moral or ‘natural’ person, and the condition of their appearance within law and political life. As he wrote in a recent collection of essays: ‘Persona originally means “mask” and it is through the mask that the individual acquires a role and a social identity’ (2009c: 71).